1994
DOI: 10.1055/s-2008-1066129
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Fundoplication in a Child

Abstract: A case of laparoscopic fundoplication is described in a child weighing 25 kg. The patient had severe skeletal deformities. Five trocars were used. The view was excellent. A complete posterior wrap was achieved without transsecting the short gastric vessels. Operating time and expenses were greater than with the conventional technique. No complications occurred. The cosmetic result was good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Although somewhat controversial [4,13,18,21,37,47], division of the short gastric vessels (SGV) is commonly performed to achieve a loose and tension-free Nissen fundoplication [7,13,17,20,24,28,35,36,44,45,47]. Previous studies have compared clipping with sharp division and ultrasonic coagulating shears for SGV division [25,41].…”
mentioning
confidence: 99%
“…Although somewhat controversial [4,13,18,21,37,47], division of the short gastric vessels (SGV) is commonly performed to achieve a loose and tension-free Nissen fundoplication [7,13,17,20,24,28,35,36,44,45,47]. Previous studies have compared clipping with sharp division and ultrasonic coagulating shears for SGV division [25,41].…”
mentioning
confidence: 99%
“…The feasibility and technical details of laparoscopic fundoplication in children have been discussed by several investigators in recent years(1‐6), but these articles do not include data on the functional assessment of the results after a minimum follow‐up. Collins et al (7) reported equally good results in 60 laparoscopic fundoplications and 60 open procedures; but again, the length of follow‐up was not given, and neither barium contrast study nor pH studies were done if patients were clinically improved.…”
Section: Discussionmentioning
confidence: 99%
“…The term peritoneoscopy was soon replaced by Pediatric Laparoscopy [5,6]. But the first publications of laparoscopic fundoplication in children date from the early nineties [7][8][9].…”
Section: Introductionmentioning
confidence: 99%